PENGARUH BEBERAPA RASIO KEUANGAN TERHADAP PREDIKSI KONDISI FINANCIAL DISTRESS - DARMINTO, .; HANDAYANI, SITI RAGIL; Atika, . (Jurnal Administrasi Bisnis, 2013)
The purpose of this research to examine financial ratios that affect financial distress condition of a firm effect of some of the financial ratios of five ratios are current ratio, profit margin, debt ratio, current liabilities to total assets, sales growth and inventory turnover in predicting financial distress conditions in textile and garment companies listed on the Stock Securities Indonesia from 2008 to 2011. Sampling technique conducted with a purposive sampling of the criteria specified then selected 14 companies in the sample, with category 0 for healthy firms and 1 for firms experiencing financial distress conditions using pre-tax loss for two consecutive years. The results using the logistic regression showed that financial ratios have to predict the potential effect of the condition of financial distress are Current ratio negatively affect the financial distress with a beta value of -8.939. Debt ratio positively affect the financial distress with a beta value of 5.305, while the current ratio negatively affect the financial distress with a beta value of -8.389. Keywords : Current Ratio, Profit Margin, Debt Ratio, Current Liabilities To Total Assets, Sales Growth, Inventory Turnover , Financial Distress